The Effectiveness of Pictures Series on Students’ Writing Skill of Procedure Text - Vanesha Grace Siregar; Junita Siahaan (Universitas Pahlawan Tuanku Tambusai, 2026)
Many junior high school students encounter difficulties in writing procedure texts, particularly in organizing ideas and presenting sequential steps coherently. This study aimed to investigate the effect of picture series media on students' writing skill in procedure texts. A quasi-experimental design involving an experimental and a control class was employed. The participants were 62 ninth-grade students of SMP Swasta Santo Petrus Medan, comprising 31 students in each class. Data were collected through pre-test and post-test writing assessments. The findings indicated that the mean score of the experimental class increased from 55.55 to 79.65, whereas the control class improved from 55.94 to 64.45. The independent samples t-test showed that the t-value was 8.149 with degrees of freedom (df) = 60. The t-table value at α = 0.05 was 1.67065. Since t-value (8.149) t-table (1.67065), and p .001, the null hypothesis was rejected. Therefore, picture series media had a significant positive effect on students' writing skill in procedure texts.